2014
DOI: 10.1186/1471-2318-14-76
|View full text |Cite
|
Sign up to set email alerts
|

Health care resource utilisation in primary care prior to and after a diagnosis of Alzheimer’s disease: a retrospective, matched case–control study in the United Kingdom

Abstract: BackgroundThis study examined medical resource utilisation patterns in the United Kingdom (UK) prior to and following Alzheimer’s disease (AD) diagnosis.MethodsA patient cohort aged 65 years and older with newly diagnosed AD between January 2008 and December 2010 was identified through the UK’s Clinical Practice Research Datalink (CPRD). Patients with a continuous record in the CPRD (formerly the General Practice Research Database [GPRD]) for both the 3 years prior to, and the 1 year following, AD diagnosis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 22 publications
3
56
2
1
Order By: Relevance
“…However, each study focused on different aspects of clinical care using different methods (Table 8). The first study showed that the AD diagnosis was associated with significant increases in primary and secondary care resources utilization (60). The second study showed that visits to dementia or mental health clinics increase the odds of receiving anti-dementia, antidepressant, and antipsychotic medications (61).…”
Section: Resultsmentioning
confidence: 99%
“…However, each study focused on different aspects of clinical care using different methods (Table 8). The first study showed that the AD diagnosis was associated with significant increases in primary and secondary care resources utilization (60). The second study showed that visits to dementia or mental health clinics increase the odds of receiving anti-dementia, antidepressant, and antipsychotic medications (61).…”
Section: Resultsmentioning
confidence: 99%
“…In a large longitudinal study conducted in the UK, AD diagnosis was associated with a significant increase in primary and secondary care resource utilization, continuing beyond diagnosis, applying equally to secondary care referrals, drug prescription (e.g., acetylcholinesterase inhibitors) and hospitalizations [6]. In an earlier case-control study also conducted in the UK, whereby cost of healthcare was compared between AD cases with varying severity levels and healthy controls, it was observed that over a period of 3 months, the average total health-related cost per control ( £ 387 or ∼$639 in January, 1999: https://fred.stlouisfed.org/data/EXUSUK.txt) was insignificant compared to the direct cost incurred by AD patients ( £ 6616 for mild AD (∼$10,907), £ 10,250 for moderate AD (∼$16,913), and £ 13,593 for severe AD (∼$22,428).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, health care expenditure ascribed to AD is expected to increase from $203 billion in 2013 to $1.2 trillion in 2050 [4]. Notwithstanding greater use of primary care services, psychiatrists, neurologists, and psychotropic medications [6, 7], evidence also shows that hospitalization risk among community-dwelling dementia patients in general is higher than non-dementia cases [8, 9], with a large portion of AD-related healthcare cost accounted for by hospital care costs [10, 11]. Evidence also points to a link between AD severity and health care costs, [1219] driven by an elongated hospital stay, [17] or more frequent home care [18].…”
Section: Introductionmentioning
confidence: 99%
“…Our results were consistent with trends found in studies from the countries with similar socioeconomic conditions as Denmark. [18][19][20][21] A study carried out in the UK study found higher rates of primary care resource utilization in an AD cohort relative to general older adult control patients both prior and preceding the AD diagnosis. 18 Similarly, a Dutch study reported increased contact frequency by preclinical dementia to their GPs more than controls.…”
Section: Discussionmentioning
confidence: 99%
“…ATET estimation for number of services used by people with AD was 3 (95% confidence interval [CI]: 2-5) from the mean of 34 (95% CI: 34-35) GP services. ATE for an average individual was 17 (95% CI: [14][15][16][17][18][19][20] in addition to the mean value of 28 services. PSM, ATE and ATET values almost coincided.…”
Section: Service Utilizationmentioning
confidence: 99%